2017
DOI: 10.1007/s00382-017-3857-9
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of extreme precipitation to temperature: the variability of scaling factors from a regional to local perspective

Abstract: interpretation of the intent and setting of the study. When this is considered, conditional scaling factors can help to better understand which influences control the intensification of rainfall with temperature on a regional scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 51 publications
3
66
0
Order By: Relevance
“…Now we use sub‐daily data to better understand the processes underlying the mutual causality of precipitation extremes and dew point temperature over shorter timescales. Hourly precipitation extremes are generally more sensitive to day‐to‐day dew point temperature variations (Drobinski et al, ; Schroeer and Kirchengast, ) and are expected to intensify at a faster rate than daily extremes in a warmer climate (Prein et al, ). We found that >91% of 1‐h rainfall extremes in Darwin (defined as >95th percentile of wet hours) were embedded within short‐duration (<12 h) storms.…”
Section: Resultsmentioning
confidence: 99%
“…Now we use sub‐daily data to better understand the processes underlying the mutual causality of precipitation extremes and dew point temperature over shorter timescales. Hourly precipitation extremes are generally more sensitive to day‐to‐day dew point temperature variations (Drobinski et al, ; Schroeer and Kirchengast, ) and are expected to intensify at a faster rate than daily extremes in a warmer climate (Prein et al, ). We found that >91% of 1‐h rainfall extremes in Darwin (defined as >95th percentile of wet hours) were embedded within short‐duration (<12 h) storms.…”
Section: Resultsmentioning
confidence: 99%
“…The increased water-holding capacity of warmer air, as governed by the Clausius-Clapeyron (C-C) relation (Lenderink and van Meijgaard, 2008;O'Gorman and Schneider, 2009;Sharma, 2015, 2017), intensifies heavy rainfall at a rate of approximately 7-8 % • C −1 of warming. On a local scale, for sub-hourly and up to 6-hourly extreme precipitation, increases at or above the C-C rate have been found in the Netherlands (Lenderink and van Meijgaard, 2008;Lenderink et al, 2017), Switzerland (Ban et al, 2014), Germany (Berg et al, 2013), the UK (Blenkinsop et al, 2015), the Mediterranean (Drobinski et al, 2016), most of Australia Sharma, 2015, 2017;Schroeer and Kirchengast, 2017), North America (Shaw et al, 2011), and China (Miao et al, 2016), while in India (Ali and Mishra, 2017) and northern Australia (Hardwick Jones et al, 2010) negative rates have been reported. The extent of urbanization also contributes to extreme regional precipitation through the urban heat island effect and aerosol concentration (Dixon and Mote, 2003;Mölders and Olson, 2004;Guo et al, 2006;Mohsen and Gough, 2012;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Annual frequencies of weather types do not show significant changes over the study period, except for a slight increase in frequency of WT1B days (0.65 days per year, 90% confidence level). Extreme convective precipitation intensities are highly sensitive to temperature in southeastern Austria (Schroeer & Kirchengast, ) and are generally expected to increase with global warming (Zhang, Zwiers, Li, Wan, & Cannon, ). Although trends in sub‐daily extreme precipitation cannot be robustly detected at this point, this means that both the frequency of convective days and the intensity of precipitation on these days could increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement among data products is high on the daily scale, but correlations decrease towards sub‐hourly observations due to the high variability on small spatio‐temporal scales and storm movement. Furthermore, sub‐daily extremes and small‐scale phenomena are not well represented in gridded precipitation datasets (Hiebl & Frei, ; Schroeer, Kirchengast & O, ).…”
Section: Methodsmentioning
confidence: 99%